1979
DOI: 10.1037/0022-0167.26.3.204
|View full text |Cite
|
Sign up to set email alerts
|

Client verbal and nonverbal reinforcement of counselor behavior: Its impact on interviewing behavior and postinterview evaluation.

Abstract: This investigation examined the effect of client reinforcement on counselor behavior within the interview as well as on selected attitudinal judgments of the counselor about the client. Thirty counselor-trainees interviewed a standard client for one 20-minute interview. Following a 10-minute baseline period, the client reinforced the counselor's reflection of feeling (RF) statements with either (a) a verbal response; (b) a verbal plus nonverbal response; or (c) a noncontingent verbal plus nonverbal response. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In addition, there was a control condition in which a noncontingent verbal-plus-nonverbal response was given. The results showed that counselors in both the verbal and verbal-plus-nonverbal conditions showed significant increases in reflection of feeling statements compared with the noncontingent controls (Lee, Hallberg, Hassard, & Haase, 1979). Although the verbalplus-nonverbal group showed an apparent superiority over the verbal group, that difference was not statistically significant.…”
Section: Reinforcement In Counseling and Employment Interviewstmentioning
confidence: 83%
“…In addition, there was a control condition in which a noncontingent verbal-plus-nonverbal response was given. The results showed that counselors in both the verbal and verbal-plus-nonverbal conditions showed significant increases in reflection of feeling statements compared with the noncontingent controls (Lee, Hallberg, Hassard, & Haase, 1979). Although the verbalplus-nonverbal group showed an apparent superiority over the verbal group, that difference was not statistically significant.…”
Section: Reinforcement In Counseling and Employment Interviewstmentioning
confidence: 83%
“…One experimental study explored patients' use of impression management strategies as a strategy to satisfy their wish to either leave or stay in a mental hospital (Braginsky, Grosse, & Ring, 1966). Some studies used trained patients who reinforced certain counselor behaviors (Dustin, 1971;Lee, Hallberg, Hassard, & Haase, 1979;McFarland et al, 2006). Friedlander and Schwartz (1985) developed a taxonomy for classifying certain patient self-presentations.…”
mentioning
confidence: 99%
“…Conversely, the client's contingent verbal and nonverbal responses may modify broadly-defined verbal behavior classes in the therapist. For example, Lee et al (1979) showed that psychotherapy trainees uttered more reflection of feeling statements when these were followed by positive verbal and nonverbal client responses.…”
Section: Toward An Experimental Analysis Of Verbal Shaping In Psychot...mentioning
confidence: 99%